2004
DOI: 10.1111/j.1460-9568.2004.03738.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling in laser‐microdissected hippocampal subregions in rat brain reveals large subregion‐specific differences in expression

Abstract: Expression profiling in the hippocampus is hampered by its cellular heterogeneity. The aim of this study was to evaluate the feasibility of using laser-microdissected hippocampal subregions for expression profiling to improve detection of transcripts with a subregion-specific expression. Cornu ammonis (CA)3 and dentate gyrus (DG) subregions were isolated from rat brain slices using laser microdissection, subjected to two rounds of linear amplification and hybridized to rat GeneChips containing approximately 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
39
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 39 publications
8
39
0
1
Order By: Relevance
“…An earlier study by Paskitti et al [15] using in situ hybridisation failed to show any significant decrease in GR mRNA in the dentate gyrus at 15, 30, 60, or 180 min after restraint stress (30 min) but did find significant decreases in all three hippocampal areas studied (dentate gyrus, CA1, and CA3) at 2 h. The lack of a dentate gyrus-specific reduction in GR mRNA after stress at earlier time points may be due to the semi-quantitative nature of in situ hybridisation. Subregional differences in hippocampal RNA expression have been previously documented and include differences in the expression of GR mRNA between the dentate gyrus and CA3 [7]. Furthermore, subregional differences in the translocation patterns of GR protein after a corticosterone stimulus have also been documented by the same group [9].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…An earlier study by Paskitti et al [15] using in situ hybridisation failed to show any significant decrease in GR mRNA in the dentate gyrus at 15, 30, 60, or 180 min after restraint stress (30 min) but did find significant decreases in all three hippocampal areas studied (dentate gyrus, CA1, and CA3) at 2 h. The lack of a dentate gyrus-specific reduction in GR mRNA after stress at earlier time points may be due to the semi-quantitative nature of in situ hybridisation. Subregional differences in hippocampal RNA expression have been previously documented and include differences in the expression of GR mRNA between the dentate gyrus and CA3 [7]. Furthermore, subregional differences in the translocation patterns of GR protein after a corticosterone stimulus have also been documented by the same group [9].…”
Section: Discussionmentioning
confidence: 85%
“…Early binding studies using micro-punched hippocampal subregions or in vitro autoradiography showed a differential localisation of MRs and GRs across hippocampal subregions [4,6]. Laser capture micro-dissection of the dentate gyrus and CA3 subregions from young male Wistar rats and subsequent gene expression profiling analysis revealed a 1.7-fold higher expression of GR in the dentate gyrus than in CA3 [7]. More detailed studies in male Sprague Dawley rats showed the same pattern of increased expression in the dentate gyrus when compared with the CA3, but similar levels when compared to the CA1 and CA2 regions [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…We and others have previously shown in rodents that these hippocampal subregions display large differences in genetic make-up, suggesting that distinct programs of gene expression underlie these subregion-specific differences in morphology, function, and vulnerability (Datson et al, 2004;Lein et al, 2004;Newrzella et al, 2007). It has also been shown that within the same subregion molecular heterogeneity exists along the dorsal-ventral axis of the hippocampus (Leonardo et al, 2006).…”
Section: Introductionmentioning
confidence: 89%
“…50,[80][81][82][83] In rodents, broad regional differences in gene expression have been reported in carefully controlled and adequately powered studies of the hippocampus. [84][85][86][87][88] Our study examined prefrontal tissue of the highest possible quality, collected at the same time of day, within a small age range from adult monkeys born and raised in the same research facility. Cluster analysis clearly identified differences between monkey dorsolateral and ventromedial prefrontal profiles of gene expression in both RMA and dChip data sets (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Many of the genes expressed in brain tissue occur at low levels 55 or are restricted to subpopulations of cells. 88 Fold-difference scores are therefore 'diluted' in microarray studies of bulk brain tissue collected by supra-cellular dissections. 42 Furthermore, microarrays tend to underestimate fold-difference scores relative to qPCR based on the 48 pairwise comparisons that we examined in monkeys.…”
Section: Discussionmentioning
confidence: 99%